Stepwise polarisation of the Drosophila follicular epithelium - Franz, André; Riechmann, Veit (Developmental biology, 2010)
The function of epithelial tissues is dependent on their polarised architecture, and loss of cell polarity is a hallmark of various diseases. Here we analyse cell polarisation in the follicular epithelium of Drosophila, an epithelium that arises by a mesenchymal-epithelial transition. Although many epithelia are formed by mesenchymal precursors, it is unclear how they polarise. Here we show how lateral, apical, and adherens junction proteins act stepwise to establish polarity in the follicular epithelium. Polarisation starts with the formation of adherens junctions, whose positioning is controlled by combined activities of Par-3, β-catenin, and Discs large. Subsequently, Par-6 and aPKC localise to the apical membrane in a Par-3-dependent manner. Apical membrane specification continues by the accumulation of the Crumbs complex, which is controlled by Par-3, Par-6, and aPKC. Thus, our data elucidate the genetic mechanisms leading to the stepwise polarisation of an epithelium with a mesenchymal origin.
Online veröffentlicht am 3. Dezember 2009
Gesehen am 13.06.2023